Azormod dynamic general equilibrium model for Azores - Fortuna, Mário (2018)
The main objective of this paper is to present a multi-sectoral, multi-regional dynamic modelling platform of the Azores economy integrated within the European and global context. The platform will have the highest capabilities of analysis and forecasting in Azores for problems related to structural sectoral and regional issues, agriculture, labour markets, public finance, trade, EU funds, regional development, environment, and energy. The modelling platform is intended to act as an analytical and quantitative support for policy-making.